Management of Geographic Tongue, Fissure Tongue, and Oral Candidiasis on Dorsum of an Elderly Smoking Patient’s Tongue - Sri Hernawati (Humanistic Network for Science and Technology (HNST), 2019)
Background: A geographic tongue is an inflammatory lesion of the tongue accompanied with atrophy formation of papilla or depapilation of the filiform papillae. The geographic tongue usually appears together with the appearance of the fissure tongue, a midline, multiple, fissure on the surface of the tongue that expands from front to back and has various patterns. Predisposing factors of geographic tongue and fissure tongue are nutritional deficiencies and stress. Oral candidiasis is one of the fungal infections that affect the oral mucosa caused by the fungus Candida albicans. Predisposing factors of oral candidiasis e.g. stress, and smoking habits. Case: 64-year-old male patient with a clinical appearance on the dorsum of the tongue in a bracelet-like form with depapilation, vertical fissure 3 mm deep and thick white plaque which could be scraped and felt painful. Diagnosis: geographic tongue, fissure tongue and oral candidiasis. Therapy: aloe vera in oral solution as antiinflammatory and analgesic, Nystatin oral suspension functions as a topical antifungal medicine, multivitamin Becomzet (Vitamin B complex, A, C, E, and Zinc) as a multivitamin. Conclusion: after therapy using aloe vera solution, nystantin becomzet controls both patients had undergone a healing process in both the case of geographic tongue, fissure tongue and oral candidiasis. Keywords: Geographic tongue, Candidasis